Estudio del proceso de compostaje de estiércol con restos vegetales provenientes de la comunidad de Pisambilla - Quishpe Yautibug, Erika Marisol (2023)
Currently, due to the accelerated population growth, there has also been an increase in food consumption. Untreated vegetable and livestock wastes have become an important source of contamination for other resources such as water and soil. The objective of this study was to compare the composting process using mixtures of cattle manure and sheep manure, together with vegetable residues (corn residues) and pruning residues (broom residues), which were evaluated as techniques to produce quality compost for use in agriculture. Within this study, a comparative analysis of the following factors was carried out: temperature, humidity, total carbon, total nitrogen, C/N ratio and a germination percentage test in order to determine the phytotoxicity of the compost. The compost was made using a system of flex foam boxes, closed with 3 perforations in the upper, middle and lower side of the box, in which a manual turning was performed in order to aerate the treatments\; during the process a daily temperature control and two weekly humidity controls were carried out. Once the comparative analysis of the 4 treatments T1 (corn residue + cattle manure), T2 (corn residue + sheep manure), T3 (broom residue + cattle manure) and T4 (broom residue + sheep manure) was carried out, it was determined that the temperature reached was adequate in each phase, it was determined that the temperature reached was adequate in each phase, as well as the humidity was between 40 to 60% and the C/N obtained was between 11.14/1 to 13.01/1, which are the optimum ranges, guaranteeing a mature compost. Thus, treatments T1, T2 and T4 showed better results compared to T3, according to the parameters evaluated, and had a seed germination rate greater than 90%. The results obtained in this study confirm that composting is a solution to treat the remains used, since once the material has been sanitized and stabilized it can be disposed of without danger for agricultural use.